UJI EKSPERIMETAL TRAJECTORY TRACKING PADA ROBOT PENJINAK BOM - Randis Randis (Politeknik Negeri Batam, 2019)
The problem of terrorism is engulfing the world has implications for the war against global terrorism. The creation of the bomb disposal robot that was able to defuse the bomb intended to create a reliable basis in all areas of security and service to humanity. The aim of this research is calculate of error trajectory tracking bomb disposal robot. This bomb disposal robot uses a caterpillar wheel using two motors with an independent control system. In addition, the robot is tested by using wireless control and navigation with line follower system. Testing is done by making two tracks on the floor surface and then test the navigation system with manual control involving two operators, then the authors implement the program control system bomb squad robot using the line sensor. The conclusion that can be decided from this research is control system by using wireless and line follower system can be used interchangeably where the value of the error for line follower system is much smaller compared with the system direct control (Bluethooth).